2018
DOI: 10.1007/s10439-018-02153-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pulmonary Venous Inflow on Cardiac Flow Simulations: Comparison with In Vivo 4D Flow MRI

Abstract: Blood flow simulations are making their way into the clinic, and much attention is given to estimation of fractional flow reserve in coronary arteries. Intracardiac blood flow simulations also show promising results, and here the flow field is expected to depend on the pulmonary venous (PV) flow rates. In the absence of in vivo measurements, the distribution of the flow from the individual PVs is often unknown and typically assumed. Here, we performed intracardiac blood flow simulations based on time-resolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 30 publications
2
42
0
Order By: Relevance
“…Our work improves over most previous computational studies of the LA flow (Bosi et al, 2018;Garcia-Isla et al, 2018;Masci et al, 2020) by considering patient-specific inflow/outflow boundary conditions, similar to Otani et al (2016). One limitation of our simulations is that PV flow rates were evenly distributed (Lantz et al, 2019). More patient-specific modeling of inflow boundary conditions would involve measuring the flow rate through each pulmonary vein (e.g., by transesophageal echocardiography) or modeling the flow impedance of each pulmonary vein based on imaging data such as vein diameter (Shi et al, 2011).…”
Section: Strengths and Limitations Of The Present Studymentioning
confidence: 91%
See 1 more Smart Citation
“…Our work improves over most previous computational studies of the LA flow (Bosi et al, 2018;Garcia-Isla et al, 2018;Masci et al, 2020) by considering patient-specific inflow/outflow boundary conditions, similar to Otani et al (2016). One limitation of our simulations is that PV flow rates were evenly distributed (Lantz et al, 2019). More patient-specific modeling of inflow boundary conditions would involve measuring the flow rate through each pulmonary vein (e.g., by transesophageal echocardiography) or modeling the flow impedance of each pulmonary vein based on imaging data such as vein diameter (Shi et al, 2011).…”
Section: Strengths and Limitations Of The Present Studymentioning
confidence: 91%
“…Since we did not have patientspecific measurements of the flow rate through each PV, Q PV was split evenly among all the PVs, i.e., Q i = Q PV (t)/4. CFD analysis with evenly split pulmonary flow rates has been previously shown to produce reasonable LA hemodynamics when compared to phase contrast MRI data (Lantz et al, 2019). To further evaluate this choice of inflow boundary conditions, we performed preliminary simulations for one of the cases comparing this approach to splitting Q PV proportionally to the area of the pulmonary veins, so that the bulk mean velocity was the same in all PVs.…”
Section: Computational Fluid Dynamicsmentioning
confidence: 99%
“…Our work improves over most previous computational studies of the LA flow [3,8,18] by considering patient-specific inflow/outflow boundary conditions, similar to Otani et al [22]. One limitation of our simulations is that PV flow rates were evenly distributed [16]. More patient-specific modeling of inflow boundary conditions would involve measuring the flow rate through each pulmonary vein (e.g., by transesophageal echocardiography) or modeling the flow impedance of each pulmonary vein based on imaging data such as vein diameter [26].…”
Section: Strengths and Limitations Of The Present Studymentioning
confidence: 80%
“…The mass flow of the pulmonary vein was defined as the boundary condition at the inlet (Figure 4). The average flow rate in a cardiac cycle was distributed to four pulmonary veins in proportion to the area of the pulmonary veins (Lantz et al, 2019). In addition, mitral orifice was defined as the outlet boundary condition of computational fluid model with average left atrial pressure (Migliavacca et al, 2003), as shown in Table 1.…”
Section: Materials and Boundary Conductionsmentioning
confidence: 99%